2003
DOI: 10.1063/1.1517152
|View full text |Cite
|
Sign up to set email alerts
|

Resonant photothermal bending spectroscopy at variable temperature 25–150 °C and its application to hydrogenated microcrystalline silicon films

Abstract: Resonant photothermal bending spectroscopy (RPBS) at various measurement temperatures has been developed for estimating absorption coefficient (α) spectra of thin film semiconductors. The experimentally obtained sensitivity of RPBS was about ten times larger than nonresonant PBS. In vacuum, this technique has been applied to estimate the α spectrum of hydrogenated microcrystalline silicon (μc-Si:H) films at the measurement temperatures from 25 to 150 °C. It is demonstrated that the temperature coefficient of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…2 by the solid line with solid circles. Those of a conventional a-Si:H film with a bandgap energy of 1.75 eV and for a microcrystalline Si film [4,5] are also indicated by solid and dashed lines, respectively. It is found that there exists extra absorption with interference fringes at 1.2-1.6 eV in the widegap a-Si:H film, an absorption coefficient a being about 10 2 cm À1 at a photon energy of 1.3 eV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 by the solid line with solid circles. Those of a conventional a-Si:H film with a bandgap energy of 1.75 eV and for a microcrystalline Si film [4,5] are also indicated by solid and dashed lines, respectively. It is found that there exists extra absorption with interference fringes at 1.2-1.6 eV in the widegap a-Si:H film, an absorption coefficient a being about 10 2 cm À1 at a photon energy of 1.3 eV.…”
Section: Resultsmentioning
confidence: 99%
“…This technique is a kind of photothermal spectroscopy, such as photoacoustic spectroscopy (PAS) and photothermal deflection spectroscopy (PDS) [6]. In brief [4,5], when light illuminates a bimorph sample constructed from a thin film semiconductor and a quartz glass substrate, a bending occurs in the sample because of thermal expansion of the film due to non-radiative recombination of photoexcited carriers. The magnitude of the bending is proportional to optical absorbance of the film.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1 shows a schematic illustration of the resonant-PBS system [2,[5][6][7]. An edge of the sample was fixed to a holder in a specially designed optical cryostat.…”
Section: Methodsmentioning
confidence: 99%
“…Resonant photothermal bending spectroscopy (resonant-PBS) [2] is a kind of photothermal spectroscopy, such as photoacoustic spectroscopy (PAS) and photothermal deflection spectroscopy (PDS) [3,4]. The resonant-PBS has an advantage which is measurable in a vacuum.…”
Section: Introductionmentioning
confidence: 99%